2016
DOI: 10.18203/2319-2003.ijbcp20164779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiling of patients with Acid Peptic Disorders (APD) in India: a cross-sectional survey of clinicians

Abstract: Background: Acid peptic disorders (APD) which include GERD and peptic ulcer disease (PUD) are common conditions reported in daily clinical practice. This survey aimed to understand the epidemiology, clinical presentation and associated overlapping comorbidities in Indian patients with APD.Methods: This was an interview based cross-sectional survey of 1000 clinicians (specialist gastroenterologists and non-specialists) across India who treated patients of APD in their practice. Information related to patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
5
2
Order By: Relevance
“…The major age group was 31 to 40 years (50%) in this study which is consistent with other studies done by Abdihamid Mohamed Ali et al 1 But some other studies showed that the prevalence of peptic ulcer disease increases with ages (>60 y). 2,3,15 In this study we found males (58.66%) were more predominant in PUD than females (41.33%). Male predominance is attributed to cigarette smoking.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The major age group was 31 to 40 years (50%) in this study which is consistent with other studies done by Abdihamid Mohamed Ali et al 1 But some other studies showed that the prevalence of peptic ulcer disease increases with ages (>60 y). 2,3,15 In this study we found males (58.66%) were more predominant in PUD than females (41.33%). Male predominance is attributed to cigarette smoking.…”
Section: Discussionsupporting
confidence: 50%
“…Similar findings were found in other studies. [1][2][3]5,6,14,15 As the study was done in peripheral settings so maximum number of patients (58.66%) came from rural areas. Their socioeconomic status remains in the medium category (54.66%).…”
Section: Discussionmentioning
confidence: 99%
“…Most common clinical presentation in our study was epigastric pain and /or burning (36%) followed by epigastric discomfort (35%) and upper gastrointestinal bleed (29%). In a study by Ramesh Roop Rai et al [16], epigastric pain/discomfort was seen in 72.3% of the patient with peptic ulcer disease. In study by khuroo et al 24 % patients presented with GI bleed [9].…”
Section: Discussionmentioning
confidence: 95%
“…Pharmacologic treatment of acid peptic disorders has focused on correcting this imbalance by either improving mucosal defences with drugs such as sucralfate, bismuth, and prostaglandin analogs, neutralizing acid with antacids, or decreasing acid secretion with histamine-2 (H2)-receptor antagonists, or, more recently, proton pump inhibitors. (2) The exact frequency of dyspepsia in the general population is difficult to find out because many individuals who have the symptoms do not seek medical care. Of all adults 30-40% experience symptoms of upper abdominal pain or discomfort but an organic cause is found in only a minority who seek medical care.…”
Section: Introductionmentioning
confidence: 99%